Is gross total removal necessary for paediatric posterior fossa tumour? - Rahman, MH; Ahamed, SU; Sayed, MA; Rashid, MH; Sarkar, S (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):239-43. The abstract of this article is available on the PubMed website